PERANCANGAN SISTEM INFORMASI LAYANAN SERVIS ELEKTRONIK RUMAH TANGGA BERBASIS WEB - Rahul Febriansyah (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2025)
The development of information technology has driven the digitalisation of various service sectors, including household electronic services. This study aims to design and develop a web-based service information system capable of replacing the manual recording process currently used by small and medium-sized enterprises. This system is designed to simplify the service recording process, track repair status, manage customer data, and generate reports automatically and in real-time. The development method used is Rapid Application Development (RAD), which emphasises rapid and iterative system development with direct user involvement at every stage. RAD consists of four main stages: requirement planning, user design, rapid construction, and cutover. System design was carried out using Data Flow Diagrams (DFD) and Entity Relationship Diagrams (ERD) to model business processes and databases. Implementation was done using web-based PHP and MySQL technology, along with a responsive interface using the Bootstrap framework. The final results of the system demonstrate improved efficiency in service management, transparency in repair processes, and easier access to information for business owners. This system is expected to serve as an effective digital solution that can be further developed according to needs